2021
DOI: 10.3390/agronomy11040652
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Yield Forecasting for the Tisza River Catchment Using Landsat 8 NDVI and SAVI Time Series and Reported Crop Statistics

Abstract: Due to the increasing global demand of food grain, early and reliable information on crop production is important in decision making in agricultural production. Remote sensing (RS)-based forecast models developed from vegetation indices have the potential to give quantitative and timely information on crops for larger regions or even at farm scale. Different vegetation indices are being used for this purpose, however, their efficiency in estimating crop yield certainly needs to be tested. In this study, wheat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…Finally, according to Al-Gaadi et al [97], Venancio et al [98], and Nagy et al [99], who found positive relations between SAVI and plant growth in potato, corn, and wheat, respectively, our study confirms the reliability of the SAVI index to give helpful information regarding plant development [6,27,28] and yield expectation also for onion crop typically characterized by sparse vegetation and a low level of soil covering.…”
Section: Relationship Between Nitrogen Fertilization Onion Yield and ...supporting
confidence: 83%
“…Finally, according to Al-Gaadi et al [97], Venancio et al [98], and Nagy et al [99], who found positive relations between SAVI and plant growth in potato, corn, and wheat, respectively, our study confirms the reliability of the SAVI index to give helpful information regarding plant development [6,27,28] and yield expectation also for onion crop typically characterized by sparse vegetation and a low level of soil covering.…”
Section: Relationship Between Nitrogen Fertilization Onion Yield and ...supporting
confidence: 83%
“…. In the study conducted in the Tisza basin in Hungary (Nagy et al, 2021), the strongest relationship (R 2 : 0.64) was observed between the NDVI data obtained from Landsat 8 images and the yield for the May-early June period when the wheat reached its peak level.…”
Section: Landsat-ndvi and Yield In Producer Fieldsmentioning
confidence: 93%
“…Remote sensing technology can quickly and accurately obtain wall-to-wall information on the land surface and has been widely used to estimate the yield of various food crops ( Ju et al., 2021 ; Maimaitijiang et al., 2021 ; Nagy et al., 2021 ). However, satellite remote sensing is often limited by low spatial resolution, long revisit period, and cloudy weather, which prevents image acquisition at certain time points ( Xu et al., 2021a ).…”
Section: Introductionmentioning
confidence: 99%